Pengaruh Current Ratio, Debt To Equity Ratio, Return On Equity terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Perdagangan Besar Barang Produksi yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2018 - Safira, Siti; Suci, Ni Made (Universitas Pendidikan Ganesha, 2021)
This study aims to examine the joint and partial effect of the current ratio, debt to equity ratio, return on equity to firm value in the large trading goods sub-sector companies listed on the IDX. The research design used is quantitative causal. The subject of this research is the sub-sector of major trading of manufactured goods listed on the IDX and the objects of this research are the current ratio, debt to equity ratio, return on equity and firm value. Data were collected by recording documents, and analyzed by multiple linear regression analysis. The results showed that: (1) Current ratio, debt to equity ratio, return on equity had a significant effect on firm value (2) Current ratio had a significant effect on firm value (3) Debt to equity ratio had a significant effect on firm value (4) Return on equity has a significant effect on firm value.